An Elderly Comorbid Patient with Atrial Fibrillation: What is Important to Know and What Should be Considered When Prescribing Anticoagulants? - T. V. Pavlova (Столичная издательская компания, 2020)
Anticoagulant therapy in elderly patients with atrial fibrillation and concomitant diseases is often the challenge for clinicians. The high risk of stroke is inherent in atrial fibrillation, and it increases when combined with coronary heart disease and chronic kidney disease. On the other hand, the comorbidity increases the risk of bleeding. Older age is also the risk factor of thrombotic and hemorrhagic complications. As a consequence, the choice of specific anticoagulant should be based on a solid evidences, obtained both from randomized clinical trials and from daily clinical practice. In the ROCKET AF trail the direct oral anticoagulant rivaroxaban showed a tendency to reduce the risk of thromboembolism by 20% compared with warfarin in the patients aged 75 years and older. The safety of rivaroxaban has been evaluated in the XANTUS POOLED program. According to the follow-up results for 12 months, more than 96% of patients didn't have any adverse event, and the number of patients with major bleeding was 1.5%. Several meta-analyzes reported a reduction of cardiovascular complications in patients treated by rivaroxaban. In the ROCKET AF trail, a "renal" dose of rivaroxaban (15 mg OD) was studied in patients with chronic kidney disease. The efficacy and safety of rivaroxaban were validated in this patients, and a simple algorithm for selecting the dose of this drug in patients with chronic kidney disease was provided.